Soil resistance to penetration and least limiting water range for soybean yield in a haplustox from Brazil - Beutler, Amauri Nelson [UNESP]; Centurion, José Frederico [UNESP]; Silva, Alvaro Pires da (Brazilian Archives of Biology and Technology, 2005)
O objetivo deste estudo foi determinar a resistência do solo à penetração (RP), o intervalo hídrico ótimo (IHO) e a densidade do solo crítica Dsc para produção de soja em Latossolo Vermelho de textura média. Os tratamentos representam a compactação do solo pela passagem do trator 0, 1, 2, 4 e 6 vezes sobre a superfície do solo, com quatro repetições, em delineamento experimental inteiramente casualizado. As amostras de solo foram coletadas nas camadas de 0,02-0,05; 0,07-0,10 e 0,15-0,18 m. A soja (Glycine max), cultivar Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA) 48, foi semeada em dezembro de 2002. Foram avaliadas a altura das plantas, número de vagens, massa seca da parte aérea, peso de 100 sementes e produtividade em área de 3,6 m². A produtividade de soja decresceu a partir da RP de 0,85 MPa e densidade do solo de 1,48 Mg m-3. O IHO foi limitado na parte superior pelo conteúdo de água na capacidade de campo (0,01 MPa) e na parte inferior pela RP, sendo a Dsc à produção de soja de 1,48 Mg m-3.

The objective of this study was determine the resistance to penetration (PR), least limiting water range (LLWR) and critical bulk density (Db-crit) for soybean yield in a medium-textured oxisol (Haplustox). The treatments represented the soil compaction by passing a tractor over the site 0, 1, 2, 4, and 6 times, with 4 replications in a randomized experimental design. Samples were collected from 0.02-0.05, 0.07-0.10 and 0.15-0.18 m depths. Soybean (Glycine max cv. Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA) 48) was sowed in December 2002. Plant height, number of pods, aerial dry matter, weight of 100 seeds, and the yield in 3.6 m² plots were recorded. Soybean yield started reduction at the PR of 0.85 MPa and Db of 1.48 Mg m-3. The LLWR was limited in highest part by water content at field capacity (0.01 MPa tension) and in lowest part by water content at PRcrit, achieved the Db-crit to yield at 1.48 Mg m-3.
Keywords: Glycine max; Water content; resistance to penetration; Bulk density